Wyoming homecoming [large type] - Palmer, Diana (Palmer, Diana. Wyoming men series., 2022)
"When Sheriff Cody Banks's wife died, he blamed Abby Brennan and made sure she knew it. He knows his behavior was likely the reason Abby left town. When he sees her at her great-uncle's funeral, Cody is determined to show her he's no longer that same angry man. Abby has studiously avoided Cody, focusing instead on raising her young niece and keeping her own family legacy alive. But when Abby inherits the property adjoining Cody's, she can't help but face the sheriff who still lingers in her memory. Circumstances keep pulling them together, but has time healed their wounds and given them a chance at a happily-ever-after?"--